ISLAMIC RELIGIOUS EDUCATION ORIENTED TOWARDS SCIENCE AND TECHNOLOGY AND ENTREPRENEURSHIP IN THE MANAGEMENT AND DEVELOPMENT OF ISLAMIC EDUCATIONAL INSTITUTIONS - Halid, Ahmad (Program Studi Pendidikan Agama Islam, 2025)
This article examines Islamic religious education oriented towards science and technology and entrepreneurship in the development of Islamic Educational Institution management. This research uses a descriptive qualitative method and data collection through observation, documentation, and interviews. The validity of the data uses the triangulation model by communicating the results of this research with the findings of at least three experts in the same field as this research. The results of this research are that (1) Islamic Religious Education survives and advances when oriented towards science and technology because science and technology are a necessity for humans in all fields of modern life, and (2) Islamic Religious Education not only teaches knowledge to students but also Islamic Educational Institutions teach teachers and students to have entrepreneurship skills as a preparation for independent, creative, and innovative living in the socio-economic field. entrepreneurship is also an effort to minimize graduate unemployment (3) Islamic religious education teaches noble morals, such as humility, respecting differences (multiculturalism), mutual cooperation, and so on.